Ethnopharmacology in the Vicinity of the Botanical Garden of the Federal University of Juiz de Fora, Brazil - Conde, Bruno Esteves; Rogerio, Izabela Taiana Salazar; de Siqueira, Aline Moreira; Ferreira, Marina Quintão; Chedier, Luciana Moreira; Pimenta, Daniel Sales (Ethnobotany Research and Applications, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> This study aimed to collect ethnopharmacological data in communities in the vicinity of the Botanical Garden of the Federal University of Juiz de Fora regarding the use of medicinal plants, and to scientifically validate the information with the scientific literature, aiming to inform the future planting of a community medicinal garden. Data and botanical material were collected with the population and key informants. The collected material was identified and registered at the CESJ herbarium. The informant community identified 104 medicinal species, with 25 species highlighted for further analysis based on consensus by a subset of key informants. The use-value and agreement regarding the main use of each species were calculated, and the primary use was validated through scientific literature. From statistical analysis and pharmacological confirmations of the listed species, we found that Mentha spicata L., Vernonanthura phosphorica (Vell.) H.Rob., and Gossypium hirsutum L. were considered the most important species relative to use-value among the 25 listed species that could be used in the proposed community medicinal garden. Sixteen species were scientifically confirmed regarding agreement and main use. Among the plants with the highest agreement taking into account the main use index, only V. phosphorica showed no concordance between popular knowledge and academic science.